2020
DOI: 10.1080/19336950.2020.1740506
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in calmodulin-binding domains of TRPV4/6 channels confer invasive properties to colon adenocarcinoma cells

Abstract: Coscoy (2020) Mutations in calmodulin-binding domains of TRPV4/6 channels confer invasive properties to colon adenocarcinoma cells, Channels, 14:1, 101-109,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
14
0
3
Order By: Relevance
“…Moreover, the functions of TRPV4 are different or even opposite in different tumors. TRPV4 plays an oncogenic role in breast cancer, endometrial cancer, gastric cancer, oral squamous cell carcinoma, and COAD ( Arbabian et al, 2020 ; Azimi et al, 2020 ; Fujii et al, 2020 ; Li et al, 2020 ; Wang et al, 2020 ) and a suppressor gene role in glioma ( Huang et al, 2021 ). However—in many other tumor types—the function of TRPV4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the functions of TRPV4 are different or even opposite in different tumors. TRPV4 plays an oncogenic role in breast cancer, endometrial cancer, gastric cancer, oral squamous cell carcinoma, and COAD ( Arbabian et al, 2020 ; Azimi et al, 2020 ; Fujii et al, 2020 ; Li et al, 2020 ; Wang et al, 2020 ) and a suppressor gene role in glioma ( Huang et al, 2021 ). However—in many other tumor types—the function of TRPV4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In COAD and ovarian cancer, TRPV4 was over-expressed; moreover, high expression levels of TRPV4 predicted worse OS in tumor patients. It has been reported that TRPV4 promotes the progression of COAD ( Arbabian et al, 2020 ), while no reports on TRPV4 in ovarian cancer are available.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functions of TRPV4 are different or even opposite in different tumors. TRPV4 plays an oncogenic role in breast cancer, endometrial cancer, gastric cancer, oral squamous cell carcinoma, and COAD [2,[9][10][11][12] and a suppressor gene role in glioma [1]. However-in many other tumor types-the function of TRPV4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In COAD and ovarian cancer, TRPV4 was overexpressed; moreover, high expression levels of TRPV4 predicted worse OS in tumor patients. It has been reported that TRPV4 promotes the progression of COAD [12], while no reports on TRPV4 in ovarian cancer are available.…”
Section: Discussionmentioning
confidence: 99%
“…Ohnologs and Diseases Ohnologs preserved in the human genome are dosage-sensitive genes [137][138][139]. Sensitivity to gene dosage may provide a key to the pathogenesis of many disorders and therefore arouses increasing interest [138].…”
Section: Clinical Significance Of Whole-genome Duplicationsmentioning
confidence: 99%